MINIMALLY INVASIVE BIPOLAR FIXATION FOR THE TREATMENT OF NEUROMUSCULAR SCOLIOSIS-MILADI’s TECHNIQUE - Aparecido Defino, Helton Luiz; Defino , Matheus P; Dorigão , Thiago (Sanamed, 2024)
This paper presents the minimally invasive bipolar technique, also known as Miladi’s technique, for the treatment of neuromuscular scoliosis. This approach involves bipolar spinal fixation extending from T1 to the pelvis. Proximal fixation is achieved using laminar and pedicular hooks configured as claws, while distal fixation employs iliosacral connectors and screws. The proximal and distal anchors are connected by a bilateral double-rod sliding construct, allowing for correction of spinal curvature and pelvic obliquity. This technique demonstrates reduced morbidity and complication rates compared to traditional methods.
Keywords: neuromuscular scoliosis; minimally invasive technique; iliosacral screws